2012
DOI: 10.1007/s00253-012-4053-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective biosorption and recovery of Ruthenium from industrial effluents with Rhodopseudomonas palustris strains

Abstract: This study demonstrated for the first time the possibility to remove and partially recover the Ruthenium contained in industrial effluents by using purple non sulfur bacteria (PNSB) as microbial biosorbents. Up to date, the biosorption was only claimed as possible tool for the removal of the platinum-group metals (PGM) but the biosorption of Ru was never experimentally investigated. The PNSBs tested have adsorbed around 40 mg g (dry biomass)(-1) of the Ru contained in the real industrial effluents. At the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Reductive precipitation of Rh has also been achieved from wastewater by a sulfate‐reducing consortium . Furthermore, Ru recovery from a plating industry wastewater was described using selective adsorption on Rhodopseudomonas palustris strains . Ru could also be recovered from acetic acid waste solution by adsorption on bacterial biomass/chitosan .…”
Section: Microbial Approaches To Recover Precious Metals From Wastesmentioning
confidence: 99%
“…Reductive precipitation of Rh has also been achieved from wastewater by a sulfate‐reducing consortium . Furthermore, Ru recovery from a plating industry wastewater was described using selective adsorption on Rhodopseudomonas palustris strains . Ru could also be recovered from acetic acid waste solution by adsorption on bacterial biomass/chitosan .…”
Section: Microbial Approaches To Recover Precious Metals From Wastesmentioning
confidence: 99%
“…Ngwenya et al demonstrated the uptake and reductive precipitation of Rh from a wastewater (PGM producer Anglo American Platinum) by a sulfate-reducing consortium and their extracted enzymes [30]. Finally, Ru recovery from a plating industry wastewater was described using selective adsorption on Rhodopseudomonas strains [31]. All of these streams contained high salt concentrations (40–300 g L −1 ) and a range of bacteriostatic metals such as Cu.…”
Section: From Biomining To Biorecoverymentioning
confidence: 99%
“…Chitosan, a biopolymer obtained by deacetylation of chitin, was reported to be a chelating adsorbent for radioactive ruthenium [11]. A microbial biosorbent, derived from Rhodopseudomonas palustris, was reported to be able to selectively remove and A c c e p t e d M a n u s c r i p t 3 recover ruthenium from effluents of Ru-plating industries, for reducing the cost of electrodeposition and environmental impact [9]. This has inspired us to look for potential biosobents for ruthenium removal from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum group metals (PGM) such as Ru, Rh, Pd, Os, Ir, and Pt are of high economic value and in great demand due to their limited abundance in earth, complex extraction procedures from ores and superior catalytic activity [9]. The solution behaviour of ruthenium is complicated due to its existence in many oxidation states and its complexation chemistry [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation